A Rare Presentation of Undiagnosed Systemic Syphilis: A Case Report and Review of Literature - Ruiz de Villa, Ariel; Haider, Asad A; Frimer, Leora; Lleshi, Amina; Bazikian, Yvette (Curēus (Palo Alto, CA), 2022)
Within the specialties of infectious diseases and dermatology, few rashes involve the palms and soles. The syphilitic rash has a pathognomonic association with these body surfaces and signals physicians to investigate this disease. However, the distinct presentations and symptoms associated with syphilis and the various stages of the disease make it diagnostically challenging. We herein report a rather intricate and unusual case of a patient who presented with a new-onset headache and blurred vision and a two-month history of diffuse pruritic maculopapular rash sparing the palms and soles. Several physicians had not established a diagnosis in the outpatient setting. Inpatient workup eventually revealed that the patient was suffering from secondary syphilis with neurological and ocular involvement. Management included a prolonged course of intravenous penicillin G leading to a complete recovery. We share images of the skin findings and the details of the intricate workup and hospital course, as well as a review of the literature.